Serum Creatinine-to-Cystatin C Ratio in the Progression Monitoring of Non-alcoholic Fatty Liver Disease - Li, Shaobo; Lu, Jing; Gu, Geng; Bai, Wenkun; Ye, Yafen; Bao, Yuqian; Yu, Haoyong; Han, Junfeng (Frontiers in Physiology, 2021)
Abstract Background: The simultaneous assessment of visceral adiposity and muscle mass might be useful to monitor the risk of nonalcoholic fatty liver disease (NAFLD) progression in large population. We aimed to investigate the value of serum creatinine-to-cystatin C ratio (CCR) in evaluating these two parameters and predicting liver steatosis and fibrosis. Methods: 154 overweight/obese inpatients (49 males, 105 females) scheduled for bariatric surgery and 49 non-overweight/obese volunteers (18 males, 31 females) responded to the hospital advertisement were involved in the cross-sectional study. Liver steatosis and fibrosis were diagnosed with transient elastography. The psoas muscle area (PMA) and visceral fat area (VFA) were measured using magnetic resonance imaging. Results: The body mass index, insulin resistance, and lipid profiles showed significant differences between the CCR tertiles. Multiple regression analyses revealed that the CCR was significantly associated with the controlled attenuation parameter (β = -0.30, P = 0.006 in males; β = -0.19, P = 0.017 in females) and liver stiffness measurements in males (β = -0.246, P = 0.044). A low CCR was associated with moderate-to-severe steatosis (P < 0.001), significant liver fibrosis (P < 0.01), and excellent predictive power for these two conditions (P < 0.01). The CCR had a negative correlation with the VFA/PMA ratio (r = -0.584, P < 0.001 in males; r = -0.569, P < 0.001 in females). Conclusions: The CCR is a serum marker for muscle-adjusted visceral fat mass, and a low CCR is associated with an increased risk of progressive NAFLD.